Teachers’ Professional Learning in the Context of Implementing Project Based Learning in a Secondary School - Sivia, Awneet; Britton, Vandy (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2021)
This study explores teachers’ professional learning (TPL) in the context of a school-wide implementation of Project Based Learning (PBL). Using phenomenology, we studied the narratives of two teachers engaged in the implementation. The questions driving this research are: How do teachers conceptualize their learning as professionals involved in a curricular innovation (in this case, PBL)?; What shifts in practice and identity occur?; What concepts are central to teachers’ professional learning?; and, What does this reveal about a stance of inquiry in professional learning? The analysis clarifies the nature of professional learning, which we articulate as a set of proposed concepts of TPL. Further connections are made between these findings about TPL and the theory of inquiry-as-stance.